Carbide complexes as π-acceptor ligands1. Issue 10 (14th October 2015) - Reinholdt, Anders; Vibenholt, Johan E.; Morsing, Thorbjørn J.; Schau-Magnussen, Magnus; Reeler, Nini E. A.; Bendix, Jesper
<x xml:space="preserve">Abstract</x> A terminal carbide complex binds as a π-acceptor towards electron-rich metal centers, mirroring CO, and provides the first homoleptic, carbide-ligated complex.